2016
DOI: 10.1111/vox.12408
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of blood donor iron deficiency and feasibility ferritin‐based iron replacement: a blood collection agency‐based study

Abstract: Iron depletion is high in frequent whole-blood donors. It is of interest to blood centres to develop ways to mitigate this risk while maintaining the current blood supply. Our feasibility study shows that blood collection agencies can measure iron stores and safely offer iron replacement in frequent blood donors with low ferritin to reduce the risk of iron depletion and future donor deferrals for low haemoglobin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 8 publications
(12 reference statements)
1
23
0
2
Order By: Relevance
“…Actionable interventions beyond education must also be considered to protect blood donors from iron deficiency . Possibilities include extending the interdonation interval, performing ferritin testing prior to donation, and providing iron supplementation . The efficacy of these interventions is well established, and there is growing evidence to support the feasibility of implementing these interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actionable interventions beyond education must also be considered to protect blood donors from iron deficiency . Possibilities include extending the interdonation interval, performing ferritin testing prior to donation, and providing iron supplementation . The efficacy of these interventions is well established, and there is growing evidence to support the feasibility of implementing these interventions.…”
Section: Discussionmentioning
confidence: 99%
“…44 Possibilities include extending the interdonation interval, 45 performing ferritin testing prior to donation, 46-50 and providing iron supplementation. 49,[51][52][53][54] The efficacy of these interventions is well established, and there is growing evidence to support the feasibility of implementing these interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that sending donors a letter with ferritin results was somewhat less efficacious than providing iron supplements, but better than placebo. In a small study performed in two US blood centers, 200 donors were consented and had ferritin levels measured; those with low ferritin were sent their results, as well as iron supplements, and deferred for 112 days . Mean ferritin had increased from 8.7 to 24.2 µg/L in the donors with low ferritin on index donation tested a mean of 4 months later; Hb deferral rates also decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the lower limit for ferritin in iron-replete men and women are comparable, and support a single, unified threshold. Prospective, non-randomized studies have found that ferritin monitoring along with recommendations to delay donation, seek medical advice, and/or take iron supplements modestly reduces the frequency of anaemia, Hb deferrals and low ferritin, with some decrease in rates of donor return (O'Meara et al, 2011;Magnussen & Ladelund, 2015;Goldman et al, 2016b;Goldman et al, 2017b) and appears to be feasible (Gorlin et al, 2016). sTfR values have been used in conjunction with ferritin measurements as a ratio, log (sTfR/ferritin) (Skikne et al, 1990;Cook et al, 2003).…”
Section: Ferritinmentioning
confidence: 99%